Applying Characteristic Mode Analysis to Systematically Design of 5G Logarithmic Spiral MIMO Patch Antenna - Ahmed Abdelaziz (IEEE, 2021)
The Theory of Characteristic Modes (TCM) provides a natural and systematic approach for designing Multiple-Input Multiple-Output (MIMO) antennas with high efficiency and uncorrelated antenna patterns. Recent progress in the growing field of MIMO antenna design, supported by TCM, is examined in this study. The challenge of designing MIMO antennas for 5G wireless communications is particularly highlighted. The results demonstrate that the characteristic modes play a key role in establishing the optimal positioning of antennas for optimal efficiency. Therefore, in this article, this theory is applied to a novel design of a logarithmic spiral patch antenna (LSPA) that is used to obtain a circular polarization with good performance more easily than traditional shapes. The systematic design process starts by designing a single element with one logarithmic spiral arm and passing through adding another arm of this single element, also passing through a two-element array antenna, and ending in four configurations of two-port MIMO and selecting the configuration with the best performance. The best configuration of the proposed MIMO provides a wide −10 dB measured impedance ranging from 27.3 GHz to 30.2 GHz, covering the whole frequency band allocated for 5G communication systems with acceptable performance as large bandwidth, high gain, high isolation, low envelope correlation coefficient, and low channel capacity loss. The isolation achieved for the operating bandwidth is better than −36 dB, demonstrating low mutual coupling. Moreover, the peak gain and total efficiency obtained are 9.9 dBi and 94%, respectively, over the whole operating bandwidth. The proposed design is designed, analyzed, and simulated in the 3D electromagnetic full-wave software, Computer Simulation Technology (CST). The design was fabricated using the photo-lithographic method and measured using the R&SZNA67 vector network analyzer. The prototype achieved is extremely similar to the expected performance and consequently proves that the offered characteristics mode analysis method is applicable.